2020
DOI: 10.3390/ijms21145121
|View full text |Cite
|
Sign up to set email alerts
|

B-Cell-Activating Factor Depletion Ameliorates Aging-Dependent Insulin Resistance via Enhancement of Thermogenesis in Adipose Tissues

Abstract: Impaired glucose tolerance is a common feature associated with human aging, which is caused by defects in insulin secretion, insulin action or both. Recent studies have suggested that B-cell-activating factor (BAFF), a cytokine that modulates proliferation and differentiation of B cells, and its receptors are expressed in mature adipocytes and preadipocytes, proposing BAFF as a potential regulator of energy metabolism. In this study, we show that systemic BAFF depletion improves aging-dependent insulin resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Interestingly, BAFF/TNFSF13B is considered as a potential anti-aging target since its concentration is particularly elevated in senescent cells and suppression of its production reduces IL6 secretion and senescent-associated phenotypes [ 34 ]. In fact, suppression of this cytokine has been suggested as a therapeutic approach to minimize aging-dependent insulin resistance [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, BAFF/TNFSF13B is considered as a potential anti-aging target since its concentration is particularly elevated in senescent cells and suppression of its production reduces IL6 secretion and senescent-associated phenotypes [ 34 ]. In fact, suppression of this cytokine has been suggested as a therapeutic approach to minimize aging-dependent insulin resistance [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…103 Another study identified higher mRNA expression of M2 macrophage markers and anti-inflammatory cytokines in the adipose tissue of BAFF deficient mice, although alterations in AT B cells were not directly examined. 104 Conversely, reconstitution of HFD fed, B cell deficient mice with B2 cells isolated from the VAT of HFD fed, wild-type mice increased the percentage of M1 polarized adipose tissue macrophages, production of IL-6 and IL1b and NFκb signaling in the recipient's VAT, and also led to impaired glucose tolerance. This elegantly demonstrating the pro-inflammatory, pathogenic phenotype of adipose B2 cells in this model of dietary-induced obesity.…”
Section: B2 Cells Promote Vat Inflammation and The Metabolic Dysregul...mentioning
confidence: 99%
“…More direct evidence of the specific effect of B2 cells was observed with the selective depletion of peripheral B2 cells in HFD mice with an anti‐B‐cell activating factor (BAFF) antibody, which reduced VAT IgG production and improved glucose tolerance 103 . Another study identified higher mRNA expression of M2 macrophage markers and anti‐inflammatory cytokines in the adipose tissue of BAFF deficient mice, although alterations in AT B cells were not directly examined 104 . Conversely, reconstitution of HFD fed, B cell deficient mice with B2 cells isolated from the VAT of HFD fed, wild‐type mice increased the percentage of M1 polarized adipose tissue macrophages, production of IL‐6 and IL1b and NF‐κb signaling in the recipient's VAT, and also led to impaired glucose tolerance.…”
Section: Role Of Vat B Cells In Regulating Vat Homeostasis and Metabo...mentioning
confidence: 99%